High affinity interactions of Pb2+ with synaptotagmin I. Issue 9 (31st July 2018) - Katti, Sachin; Her, Bin; Srivastava, Atul K.; Taylor, Alexander B.; Lockless, Steve W.; Igumenova, Tatyana I.
Abstract : Pb 2+ binds C2 domains with high affinity, desensitizes them to Ca 2+, and supports their membrane interactions. Abstract : Lead (Pb) is a potent neurotoxin that disrupts synaptic neurotransmission. We report that Synaptotagmin I (SytI), a key regulator of Ca 2+ -evoked neurotransmitter release, has two high-affinity Pb 2+ binding sites that belong to its cytosolic C2A and C2B domains. The crystal structures of Pb 2+ -complexed C2 domains revealed that protein-bound Pb 2+ ions have holodirected coordination geometries and all-oxygen coordination spheres. The on-rate constants of Pb 2+ binding to the C2 domains of SytI are comparable to those of Ca 2+ and are diffusion-limited. In contrast, the off-rate constants are at least two orders of magnitude smaller, indicating that Pb 2+ can serve as both a thermodynamic and kinetic trap for the C2 domains. We demonstrate, using NMR spectroscopy, that population of these sites by Pb 2+ ions inhibits further Ca 2+ binding despite the existing coordination vacancies. Our work offers a unique insight into the bioinorganic chemistry of Pb(ii ) and suggests a mechanism by which low concentrations of Pb 2+ ions can interfere with the Ca 2+ -dependent function of SytI in the cell.